Workplace telepressure and work–life balance outcomes: The role of work recovery experiences. (30th May 2019) - Barber, Larissa K.; Conlin, Amanda L.; Santuzzi, Alecia M.
Abstract: Workplace technology has posed some challenges to worker well‐being. This research examined how workplace telepressure—a preoccupation and urge to respond quickly to message‐based communications—is related to work life balance evaluations, as well as how work recovery experiences might explain this relationship. Using an online survey design, Study 1 ( N  = 254) and Study 2 ( N  = 409) demonstrated that employees' workplace telepressure negatively related to satisfaction with work–life balance. Study 1 showed that psychological detachment may explain the relationship between workplace telepressure and satisfaction with work–life balance. In Study 2, psychological detachment and control over leisure time explained the relationship between workplace telepressure and global evaluations of work–life balance (satisfaction and effectiveness). Mastery and control experiences explained the relationship between workplace telepressure and work–family enrichment. Lastly, three recovery mechanisms (detachment, relaxation, and control) explained the link between workplace telepressure and work–family conflict. The evidence suggests that workplace telepressure is negatively associated with various employee evaluations of work–life balance, but the role of recovery experiences may depend on how work–life balance is measured.